Attribution Model of Composition in Modern Chinese (On the Example of Medical Terms) - Akmalovna, Sultanova Lola (International Journal of Psychosocial Rehabilitation, 2020)
This articleanalyses the two-syllabic medical terms of the modern Chinese language, formed by the attributive model of compounding. This model within the framework of this lexico-semantic group has not been the subject of a special study yet. Thus, the linguistic units formed by this model were the material for solving the problem of systematizing ideas about speech formation. Terms are special concepts. Their specificity is based on the fact that, first of all, they do not lose their integrity, no matter how their content is transmitted. Regardless of whether the terms are monosyllabic words or polysyllabic phrases, they always represent one sign to which one concept corresponds. The main difference between the term and the common word is the specialized meaning of the term. Terms are commonly used in special areas of communication to mean expressing special concepts. Word- formation models are within the framework of the leading method of word-formation-compounding in the Chinese language. The medical terminology of modern Chinese is a kind of terminology. As you know, between the concepts of “word” and “term” there are certain lexical differences. Compound words - a product of collocation and lexicalization of phrases, consist entirely of root (significant) morphemes. The most productive class of compound words is two-syllable words consisting of two-root (significant) morphemes that are in certain relations. In medical terminology of modern Chinese language attribution model of compounding is the most effective. With the subordinate connection of the attributive model between the parts of a compound word, one part is subordinate to the other, and both parts, therefore, are in different semantic dependence. Subjunctive addition is a combination of morphemes, unequal in semantic and functionally syntactic relations. Most of the terms formed by the attributive model of word formation are noun terms, collocation terms, and borrowing terms.